Comparative Analysis of Flood Hydrograph Way Kandis River Basin with Synthetic Units Hydrograph (HSS) Snyder, Nakayasu, and Limantara Methods - I Yuliansyah; Aprizal Aprizal; A Nurhasanah (International Conference on Engineering and Technology Development (ICETD), 2017)
Hydrological data is not available in most areas of Lampung Province. To decrease the unit hydrograph, then it’s made a Synthetic Unit Hydrograph is created based on the physical characteristics of the River Basin. Way Kandis River which is a creek of Way Sekampung River is one of the watershed that does not have unit hydrograph so it is necessary to make HSS calculation from some existing method. The design flood debits calculated in this study were Q2, Q5, Q10, Q20, Q25, Q50, and Q100 using the HSS Snyder Method, the Nakowsasu HSS Method and the Limantara HSS Method. The peak debit (Qp) results on the highest 100 year (Q100) recalculation on the Limantara Q100 method = 615.44 m3 / sec HSS by a margin of less than 5 m3 / s through the Snyder Q100 method = 610.79 m3 / s. Lowest Method Nakayasu Q100: 437,40 m3 / s. The time to reach the longest peak (Tp) discharge on the Snyder method = 8 hours by 1 hour difference in each method. Nakayasu Method = 7 hours and Limantara Method = 6 hours. Of the three methods HSS can not yet predicted which approach approaches the flood hydrograph in Way Kandis watershed because there is no data for calibration. Therefore, further research is needed to obtain measurable flow data on Way Kandis River